2017
DOI: 10.29252/sjrm.2.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility Effective Factors and Failure Type Determination in Iranian Infertile Men

Abstract: Incidence and main causes of infertility in a resident population ... [8] Semen quality and age-specific changes: A study between two ... [9] Semen quality in fertile US men in relation to geographical ... [10] Sexual, marital, and social impact of a man's perceived ... [11] Evaluation of the subfertile ... [12] Clinical relevance of oxidative stress in male ... [13] Chronic prostatitis and male accessory gland infection-is there an impact on ... [14] Semen analysis in laboratory practice: An overview ... [15]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a meta-analysis of Iranian studies, the prevalence of male infertility was reported as 2% ( 11 ). According to Agarwal et al, 2.5% to 12% of infertility cases are due to the male factor ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis of Iranian studies, the prevalence of male infertility was reported as 2% ( 11 ). According to Agarwal et al, 2.5% to 12% of infertility cases are due to the male factor ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported the prevalence of male infertility, most have been conducted on the population who referred to infertility centers (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaires were compared and reviewed by several experts in psychology in terms of appearance of the questionnaire, the use of proper words, and the use of proper grammar. This self-report questionnaire included 20 questions in 4 dimensions including: cognitive dimension (questions of 2,9,12,16,17), physiologic dimension (questions of 1, 4, 5, 6, 14), emotional dimension (questions of 3,11,15,18,20) and behavioral dimension (items of 7,8,10,13,19). The score range of each question was from 0 to 2 points (0 = never, 1 = sometimes, and 2 = always).…”
Section: Partmentioning
confidence: 99%
“…Nonoccurrence of pregnancy during one year of sexual intercourse is known as infertility without the use of prevention methods (2). About 15% of couples are infertile (3). Over the world, above 70 million pairs suffer from infertility, in which most of them belong to developing countries (4).…”
Section: Introductionmentioning
confidence: 99%